Involvement of Male Partners in Skilled Birth Care in the North Dayi District, Ghana. (1st July 2019) - Saah, Farrukh Ishaque; Tarkang, Elvis Enowbeyang; Komesuor, Joyce; Osei, Eric; Acquah, Evelyn; Amu, Hubert
Abstract : Background. With more than half of the global maternal deaths occurring in sub-Saharan Africa, skilled attendance during childbirth is essential in achieving safer births and lower maternal mortalities. Given that societal ascriptions of gender roles strongly influence the utilisation of skilled care by women, male partner involvement in skilled birth is essential. We explored male partner involvement in skilled birth at the North Dayi District of Ghana. Methods. This qualitative study interviewed 14 mothers and their male partners, together with two health professionals. The participants were purposively recruited using in-depth interviews. Data collected were analysed manually, but thematically. Result. Male partners had inadequate knowledge of childbirth and the skilled birth process as well as possible complications arising during delivery. Even though the male partners demonstrated positive perception towards skilled birth and their involvement in the process, their actual involvement in skilled birth care was generally low. Factors which inhibited most of the male partners from getting involved in skilled birth care were health facility nonconduciveness and occupation. However, motivations to do so were marital commitment and sense of responsibility, past experience, nearness to health facility, and safety and survival of partner and baby. Conclusion. These findings imply that Ghana may not be able to meet the Sustainable Development Goal Three target of reducing its maternal mortality ratio from 216 to below 70 per 100, 000 live births by 2030. Stakeholders in Ghana's health industry need to develop male accommodating skilled birth policies and approaches to promote male involvement in skilled birth care.